Facilitating collaboration and partnerships: lessons from adaptive collaborative management in the Philippines - Hartanto, H. (2003)
Community forestry has a long history in the Philippines. It began as early as in the 1970s, when the government started a people-oriented forestry initiative in the country. Three decades of experience have led to the creation of a flagship programme called Community-Based Forest Management (CBFM) in 1995. Nevertheless, devolution and decentralisation also create complexity and confusion. With authorities, rights and responsibilities being shared among various government agencies and communities, a greater number of 'groups' emerged with different and sometimes conflicting interests, objectives, mandates and values. In the midst of these institutional and management complexities we carried out a research project on Adaptive Collaborative Management (ACM) in two CBFM sites in the Philippines. The ACM approach, which focuses on social learning, communication and collective action among diverse stakeholders, was used to facilitate collaboration and learning among the People's Organisations (PO), DENR and other local stakeholders in the Philippines. Our three years of work on ACM implementation revealed improvements in human and social capital that indicate increased collaboration and partnerships in action and learning within and across stakeholders. Some of the improvements observed include: PO members jointly planned their action in a more strategic way; increased joint action within the PO members (and the revival of the local culture of bayanihan and pahina) and across stakeholders; development of a monitoring system which was designed and developed by the PO, DENR and other local stakeholders in Palawan; the PO members monitored their actions in a more structured and conscious way; increased experimentation by PO members, such as in establishing cut flower nursery, handicraft making and herbal medicine processing, that allowed them to learn the best option and minimise risks.